Metropolitan centres. Urban fringe landscape protection and planning - Laukaitytė-Malžinskienė, Giedrė I. (Journal of Architecture and Urbanism, 2012)
The paper considers requirements of the European Landscape Convention as well as obligations of Lithuania in the field of implementation of such requirements. Furthermore, it discusses advancing general and concrete political and legal tools, which are imposed on the national landscape protection, regulation and planning. Landscape protection is proposed to orient towards protection and maintenance of characteristic features, while sustainable development is achieved via landscape planning. The important problems of metropolitan centre fringe landscape formation are analysed. While preparing general plans of cities and district municipalities, district landscape plans give insufficient attention to preservation of landscape characteristics. That is the reason tools for integrated landscape protection and urban development have been proposed in the paper as well as ways for their implementation into the national planning practice. With the help of these tools, land proprietors and urban planners will better understand the influence of proposed decisions on landscape and determine the most suitable urban development forms in the metropolitan fringes. Sustained metropolitan fringe development should be supported by the criterion of landscape protection. It has to implement life quality aspirations of people living both in cities and districts.Article in Lithuanian.Metropolinių centrų priemiesčio kraštovaizdžio apsaugos ir planavimo klausimaiSantrauka. Svarstomi Europos kraštovaizdžio konvencijoje keliami reikalavimai, Lietuvos įsipareigojimai juos įgyvendinti tobulinant bendro ir konkretaus pobūdžio politines ir teisines priemones, skirtas šalies kraštovaizdžiui apsaugoti, tvarkyti ir planuoti. Straipsnyje kraštovaizdžio apsaugą siūloma orientuoti į būdingų kraštovaizdžio ypatybių išsaugojimą ir palaikymą, kai tvarios plėtros siekiama planuojant kraštovaizdį. Aptariamos opios metropolinių centrų priemiesčio kraštovaizdžio formavimo problemos. Rengiant miestų ir rajonų savivaldybių bendruosius planus, rajoninius Kraštovaizdžio planus, priemiesčio kraštovaizdžio charakterio išsaugojimo klausimai nepakankamai respektuojami, todėl siūlomas integruotų kraštovaizdžio apsaugos ir užstatymo plėtros priemonių sukūrimas ir jų įdiegimas į šalies planavimo praktiką. Taikydami šias priemones žemės valdytojai ir projektuotojai geriau suprastų siūlomų sprendinių poveikį kraštovaizdžiui, nustatytų tinkamiausias priemiesčio užstatymo formas, jas harmoningai įterpdami į kraštovaizdinį kontekstą. Kraštovaizdžio apsaugos kriterijumi paremta tvari priemiesčių plėtra turėtų tapti priemone, padedančia įgyvendinti tiek miesto, tiek rajono gyventojų gyvenimo kokybės siekius.Reikšminiai žodžiai: didmiestis, priemiestis, metropolinis arealas, metropolizacija, tvari plėtra, kraštovaizdžio charakteris.